Developing novice teachers practice through critical reflection - Nguyen , Thanh Ly (Tạp chí Khoa học Trường Đại học Sư phạm Thành phố Hồ Chí Minh, 2019)
Group work and leadership skills are essential skills of 21st-century students. For students to develop these skills well, teacher students and teachers need to be trained and practice proficiency at schools. This study was conducted to show how group teaching in university was practiced in schools. The study is carried out in two phases: at VNU University of Education firstly when observing students’ teacher classrooms and secondly students’ classroom at primary/ secondary schools. The findings of the study are used to suggest guidance for good practice in leadership and management training courses in Vietnam.